Hyperleukocytosis, leukemoid reaction caused by malignant peritoneal mesothelioma: a case report and review of literature - Zhu, Kaibo; Zhou, Dan; Liu, Kang; Wu, Lingzhen; Jin, Juan; Luo, Zimian (Frontiers in Oncology, 2025)
Paraneoplastic leukemoid reaction (PLR)-induced hyperleukocytosis remains a critical diagnostic challenge. Malignant peritoneal mesothelioma, known for its nonspecific clinical presentation, often evades early detection. We report a 75-year-old male with cirrhosis presenting with fever (38.2°C), progressive ascites, leukocytosis (109.9×109/L), and elevated CRP (247.41 mg/L). Initial diagnosis of spontaneous peritonitis failed to explain the leukocytosis, prompting bone marrow examination, including cytomorphology and genetic analysis, which turned out do not support a diagnosis of leukemia or myeloproliferative neoplasms. Subsequent peritoneal biopsy confirmed diffuse malignant peritoneal mesothelioma. Despite prompt diagnosis, the patient developed progressive multi-organ dysfunction and died on day 14. This case underscores the imperative to consider PLR as a potential cause of hyperleukocytosis in oncological contexts, rather than attributing it solely to hematological malignancies. Moreover, it highlights the importance of considering malignant peritoneal mesothelioma in the differential diagnosis of unexplained ascites and peritoneal thickening. Additionally, we propose the hypothesis that glucocorticoids may hold therapeutic potential in the management of PLR.